Polylactic acid fiber antibacterial film as well as preparation method and application thereof
By loading titanium dioxide particles on the polylactic fiber membrane, photocatalytic technology is used to inhibit bacterial growth, solving the problems of fiber membrane aging and low filtration efficiency, and achieving efficient filtration and antibacterial effects.
Patent Information
- Application Number
- CN202411478892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-31
AI Technical Summary
During use, polylactic fiber filter membranes are prone to adsorb microorganisms, resulting in bacterial growth, and then aging and damage. The service cycle is short. It is difficult for the prior art to take into account both antibacterial efficiency, filtration efficiency and fracture strength.
Using polylactic fiber antibacterial membrane, by defining the diameter ratio and composition of the first fiber and the second fiber, a uniformly distributed fiber structure is formed, and titanium dioxide or modified titanium dioxide particles are tightly supported on the fiber surface, and the active substance is inhibited by photocatalytic generation. Bacterial growth.
A polylactic fiber antibacterial membrane with high antibacterial efficiency and high filtration efficiency has been achieved, extending the service cycle of the fiber membrane and improving mechanical properties and breathability.
Smart Images

Figure CN119215697A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber filtration membranes, and in particular to a polylactic acid fiber antibacterial membrane and a preparation method and application thereof. Background Art
[0002] Particulate matter (PM) in the air has a huge negative impact on human health and global climate. PM can be divided into coarse components (PM with a diameter <10 μm) according to its diameter. 10 ), fine components (PM with a diameter <2.5 μm 2.5 ) and ultrafine components (UFPS with a diameter of <0.1μm), these particles can penetrate the respiratory system, cause health hazards, and have an impact on global climate and air quality. Due to their small mass, they are difficult to separate from other substances in the gas, and a filter medium is urgently needed to remove these particles.
[0003] Polylactic acid has good application prospects in the field of air filtration due to its good biodegradability. However, the filter membrane formed by polylactic acid easily adsorbs microorganisms, causing bacteria to grow on the surface or inside the membrane. As the use time increases, the filter membrane will age and break, and the service life will become shorter.
[0004] Therefore, how to provide a polylactic acid fiber antibacterial film with high antibacterial efficiency is a technical problem to be solved urgently in this field. Summary of the invention
[0005] The main purpose of the present invention is to provide a polylactic acid fiber antibacterial membrane and a preparation method and application thereof, so as to solve the problem of poor antibacterial efficiency of the filtration membrane in the prior art.
[0006] In order to achieve the above object, according to one aspect of the present invention, a polylactic acid fiber antibacterial film is provided, the polylactic acid fiber antibacterial film comprising a first fiber, a second fiber and antibacterial particles, the first fiber and the second fiber are randomly stacked, and the antibacterial particles are loaded on the surface of the first fiber and the second fiber;
[0007] The diameter ratio of the first fiber to the second fiber is 1:(11-30), and the average diameter of the antibacterial particles is 10-100 nm; the first fiber and the second fiber both include polylactic acid, and the material of the antibacterial particles is titanium dioxide and / or modified titanium dioxide.
[0008] Furthermore, the modified titanium dioxide is silver-doped titanium dioxide; the mass content of silver in the silver-doped titanium dioxide is 0.1% to 5%;
[0009] Furthermore, the preparation of silver-doped titanium dioxide includes: mixing a titanium source, a silver salt and water, and performing microwave treatment to obtain silver-doped titanium dioxide.
[0010] Furthermore, the mass ratio of the titanium source to the silver salt is (2-12):1.
[0011] Furthermore, the titanium source includes at least one of titanium sulfate, titanium hydroxide, titanium chloride, ethyl titanate, diisopropyl titanate, isopropyl titanate, and tetrabutyl titanate.
[0012] Preferably, the silver salt comprises at least one of silver nitrate, silver chloride, silver carbonate, silver ammonia solution, silver hydroxide, silver citrate, and silver alkoxide;
[0013] Preferably, the microwave treatment has a power of 500-1500 W, a temperature of 100-200° C., and a time of 20-120 min.
[0014] Further, the mass ratio of the first fiber, the second fiber and the antibacterial particles is 1:(0.2-2):(0.25-4); and / or,
[0015] The thickness of the polylactic acid fiber antibacterial film is 20 to 600 μm.
[0016] Furthermore, the diameter of the first fiber is 30-800 nm, and the average pore size is 1-25 nm; and / or the diameter of the second fiber is 1-10 μm, and the average pore size is 2-50 nm.
[0017] Further, the first fiber and the second fiber both include left-handed polylactic acid and right-handed polylactic acid;
[0018] Preferably, the first fiber comprises a first left-handed polylactic acid and a first right-handed polylactic acid, and the second fiber comprises a second left-handed polylactic acid and a second right-handed polylactic acid;
[0019] wherein the molar ratio of the second L-polylactic acid to the second D-polylactic acid is greater than the molar ratio of the first L-polylactic acid to the first D-polylactic acid;
[0020] Preferably, the molar ratio of the first L-polylactic acid to the first D-polylactic acid is (5-10):1;
[0021] Preferably, the molar ratio of the second L-polylactic acid to the second D-polylactic acid is (10-15):1.
[0022] The second aspect of the present invention provides a method for preparing the polylactic acid fiber antibacterial film of the first aspect, comprising the following steps:
[0023] The first spinning solution, the second spinning solution and the antibacterial particle dispersion are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film;
[0024] The first spinning solution and the second spinning solution both contain polylactic acid, the antibacterial particle dispersion contains titanium dioxide and / or modified titanium dioxide, and the mass fraction of polylactic acid in the second spinning solution is greater than the mass fraction of polylactic acid in the first spinning solution.
[0025] Furthermore, the preparation method of the first spinning solution includes:
[0026] Dissolving the first polylactic acid in a first solvent to obtain a first spinning solution;
[0027] The preparation method of the second spinning solution comprises:
[0028] dissolving the second polylactic acid in a second solvent to obtain a second spinning solution;
[0029] Preferably, the first polylactic acid and the second polylactic acid both include left-handed polylactic acid and right-handed polylactic acid;
[0030] Preferably, the first polylactic acid includes a first left-handed polylactic acid and a first right-handed polylactic acid, and the second polylactic acid includes a second left-handed polylactic acid and a second right-handed polylactic acid; wherein the molar ratio of the second left-handed polylactic acid to the second right-handed polylactic acid is greater than the molar ratio of the first left-handed polylactic acid to the first right-handed polylactic acid;
[0031] Preferably, the molar ratio of the first L-polylactic acid to the first D-polylactic acid is (5-10):1;
[0032] Preferably, the sum of the mass fractions of the first L-polylactic acid and the first D-polylactic acid in the first spinning solution is 5% to 10%;
[0033] Preferably, the first solvent includes a first good solvent and a first non-good solvent, and the volume ratio of the first good solvent to the first non-good solvent is 1:(2.5-4.5);
[0034] Preferably, the molar ratio of the second L-polylactic acid to the second D-polylactic acid is (10-15):1;
[0035] Preferably, the sum of the mass fractions of the second right-handed polylactic acid and the second left-handed polylactic acid in the second spinning solution is 10% to 20%;
[0036] Preferably, the second solvent includes a second good solvent and a second non-good solvent, and the volume ratio of the second good solvent to the second non-good solvent is 1:(5.5-8.5);
[0037] Preferably, the first good solvent and the second good solvent each independently include at least one of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate, and tetrahydrofuran, and the first non-good solvent and the second non-good solvent each independently include at least one of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol, and propylene glycol.
[0038] Furthermore, the preparation method of the antibacterial particle dispersion comprises:
[0039] mixing titanium dioxide and / or silver-doped titanium dioxide, a dispersant and a third solvent to obtain an antibacterial particle dispersion;
[0040] Preferably, the dispersant includes at least one of polyvinyl pyrrolidone, dodecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate;
[0041] Preferably, the third solvent includes at least one of water, dimethylformamide, dichloromethane, chloroform, N-methylpyrrolidone, hexafluoroisopropanol, methanol, ethanol, isopropanol, and glycerol;
[0042] Preferably, the mass ratio of titanium dioxide and / or silver-doped titanium dioxide to the dispersant is 1:(20-80);
[0043] Preferably, the mass fraction of titanium dioxide and / or silver-doped titanium dioxide in the antibacterial particle dispersion is 0.15% to 1%.
[0044] Further, in the multi-needle electrospinning process, the metal nozzles loaded with the first spinning solution, the second spinning solution and the antibacterial particle dispersion are the first nozzle, the second nozzle and the third nozzle respectively;
[0045] Preferably, the inner diameter of the first nozzle is 10-20 μm, the inner diameter of the second nozzle is 60-80 μm, and the inner diameter of the third nozzle is 30-60 μm;
[0046] Preferably, the voltages of the first nozzle, the second nozzle and the third nozzle are all 10 to 30 kV;
[0047] Preferably, the consumption rate of the first spinning solution is 0.5 to 2 mL / h, the consumption rate of the second spinning solution is 0.2 to 1.2 mL / h, and the consumption rate of the titanium dioxide dispersion is 0.2 to 1.5 mL / h;
[0048] Preferably, the receiving distances of the first nozzle, the second nozzle and the third nozzle are all 10-25 cm.
[0049] The third aspect of the present invention provides an air filter, comprising the polylactic acid fiber antibacterial membrane provided by the first aspect or the polylactic acid fiber antibacterial membrane prepared by the preparation method provided by the second aspect.
[0050] By applying the technical solution of the present invention, on the one hand, by limiting the composition and diameter ratio of the first fiber and the second fiber, the fibers are evenly distributed, the porosity and fiber distribution density of the fiber filter membrane are optimized, thereby improving the filtration performance of the fiber filter membrane; on the other hand, by utilizing antibacterial particles of a specific material tightly loaded on the fiber surface, titanium dioxide or modified titanium dioxide can form photogenerated holes with super oxidizing ability and photogenerated electrons with super reducing ability under the action of light, and the photogenerated holes or photogenerated electrons combine with H2O or O2 to generate active substances such as hydroxyl radicals and superoxide ion radicals, which can effectively inhibit the growth of bacteria, thereby obtaining a polylactic acid fiber antibacterial membrane with both high antibacterial efficiency and high filtration efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a SEM image of the polylactic acid fiber antibacterial film in Example 1 of the present invention;
[0052] Figure 2 This is a SEM image of the polylactic acid fiber antibacterial film in Example 4 of the present invention;
[0053] Figure 3 This is a SEM image of the polylactic acid fiber membrane in Comparative Example 2 of the present invention;
[0054] Figure 4 This is the SEM image of the polylactic acid fiber membrane in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0056] As described in the background of the present invention, it is difficult for the polylactic acid fiber antibacterial membrane in the prior art to take into account the problems of breaking strength, surface potential, antibacterial efficiency and filtration efficiency. In order to solve the above problems, the first aspect of the present invention provides a polylactic acid fiber antibacterial membrane, which includes a first fiber, a second fiber and antibacterial particles, the first fiber and the second fiber are randomly stacked, and the antibacterial particles are loaded on the surface of the first fiber and the second fiber; wherein the diameter ratio of the first fiber to the second fiber is 1: (11-30), and the diameter of the antibacterial particles is 10-100nm; the first fiber and the second fiber both include polylactic acid, and the material of the antibacterial particles is titanium dioxide and / or modified titanium dioxide.
[0057] The polylactic acid fiber antibacterial film of the present invention comprises a matrix and antibacterial particles. The matrix is a film formed by randomly stacking the first fiber and the second fiber, which can be realized by an electrostatic spinning process. Specifically, the first fiber and the second fiber are continuous straight filaments, oriented to be randomly distributed, so as to form a film with a mesh structure. The antibacterial particles are composed of titanium dioxide and / or silver-doped titanium dioxide, which are individually loaded on the surface of the first fiber and the second fiber.
[0058] Among them, the first fiber and the second fiber have the same composition, both of which include polylactic acid. The polylactic acid molecular chains are stacked to form a polylactic acid stereocomplex, which has good interfacial compatibility, high crystallinity and well-arranged microstructure, thereby improving the mechanical properties and filtration performance of the polylactic acid fiber antibacterial membrane. The diameter ratio of the first fiber to the second fiber is 1: (11-30), for example, 1: 11, 1: 15, 1: 20, 1: 25, 1: 30 or a range composed of any two of them. The fiber filter membrane formed by fibers of a single order of magnitude has certain defects in filtration efficiency and air resistance. The present invention can make the fibers in the polylactic acid fiber antibacterial membrane evenly distributed by limiting the first fiber and the second fiber to have the same composition and the diameter ratio within the above range, while improving the porosity and fiber distribution density of the polylactic acid fiber antibacterial membrane, thereby improving the filtration performance of the fiber filter membrane for particulate matter.
[0059] Titanium dioxide is an inorganic compound with photocatalytic properties, which can decompose organic matter under the ultraviolet rays of sunlight. Modified titanium dioxide is made by doping metals or non-metals in titanium dioxide. For example, metals such as aluminum, platinum, and silver can be doped. Using the antibacterial particles tightly loaded on the surface of the fiber, the surface of titanium dioxide or modified titanium dioxide is excited under the action of light, and the electrons undergo energy level transitions, forming photogenerated holes with super strong oxidation ability and photogenerated electrons with super strong reduction ability. The photogenerated holes or photogenerated electrons combine with H2O or O2 to generate active substances such as hydroxyl free radicals and superoxide ion free radicals. These active substances can effectively inhibit the growth of bacteria, thereby obtaining a polylactic acid fiber antibacterial film with both high antibacterial efficiency and high filtration efficiency.
[0060] The average diameter of the antibacterial particles is 10 to 100 nm, for example, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 100 nm or any two thereof, and the average diameter of the antibacterial particles can also be understood as the D50 particle size of the antibacterial particles. That is, the antibacterial particles are nano-level, and the nano-level antibacterial particles have a large surface area, increase the contact area, and maximize their inhibitory effect on bacterial growth.
[0061] According to the research of the present invention, on the one hand, by limiting the composition and diameter ratio of the first fiber and the second fiber, the fibers are evenly distributed, the porosity and fiber distribution density of the fiber filter membrane are optimized, thereby improving the filtration performance of the fiber filter membrane; on the other hand, by utilizing antibacterial particles of a specific material tightly loaded on the fiber surface, titanium dioxide or modified titanium dioxide can form photogenerated holes with super oxidation ability and photogenerated electrons with super reduction ability under the action of light, and the photogenerated holes or photogenerated electrons combine with H2O or O2 to generate active substances such as hydroxyl radicals and superoxide ion radicals, which can effectively inhibit the growth of bacteria, thereby obtaining a polylactic acid fiber antibacterial membrane with both high antibacterial efficiency and high filtration efficiency.
[0062] In some embodiments, the modified titanium dioxide is silver-doped titanium dioxide. Silver doping can improve the light absorption performance of titanium dioxide, and silver nanoparticles can penetrate and kill bacteria by attaching to the cell membrane, so that the silver-doped titanium dioxide has stronger antibacterial activity, thereby further improving the antibacterial efficiency of the polylactic acid fiber antibacterial film. In addition, by introducing silver-doped titanium dioxide, the mechanical properties of the polylactic acid fiber antibacterial film, such as breaking strength, can be enhanced, which makes the polylactic acid fiber antibacterial film have better performance under high load and harsh environmental conditions.
[0063] The present invention does not limit the doping amount of silver. In practical applications, the doping amount of silver can be optimized according to specific needs and reaction conditions. The higher the silver doping amount in silver-doped titanium dioxide, the stronger the light absorption performance and antibacterial activity of titanium dioxide. However, too high a silver doping amount may lead to performance degradation and increased cost. In some embodiments, the mass content of silver in silver-doped titanium dioxide is 0.1% to 5%, for example, 0.1%, 1%, 2%, 3%, 4%, 5% or a range composed of any two of them.
[0064] Titanium dioxide and / or silver-doped titanium dioxide can be obtained by commercial purchase or conventional preparation methods. In some embodiments, the preparation method of silver-doped titanium dioxide includes: the preparation of silver-doped titanium dioxide includes: mixing a titanium source, a silver salt and water, and subjecting the mixture to microwave treatment to obtain silver-doped titanium dioxide. Among them, the preparation of silver-doped titanium dioxide can be achieved by microwave assistance to improve the yield. In some preferred embodiments, the power of microwave treatment is 500-1500W, the temperature is 100-200°C, and the time is 20-120min. In addition, the mass content of silver in silver-doped titanium dioxide can be adjusted by adjusting the amount of raw materials added. In some embodiments, a titanium source is mixed with water to obtain a titanium source solution; the titanium source solution is mixed with a silver salt and microwave treated to obtain silver-doped titanium dioxide, and the mass ratio of the titanium source solution to the silver salt is (2-12):1, for example, 2:1, 3:1, 5:1, 7:1, 9:1, 12:1 or a range consisting of any two of them.
[0065] The present invention does not limit the specific type of raw materials, and can be adjusted and obtained according to actual needs. In some embodiments, the titanium source includes at least one of titanium sulfate, titanium hydroxide, titanium chloride, ethyl titanate, diisopropyl titanate, isopropyl titanate, and tetrabutyl titanate; the silver salt includes at least one of silver nitrate, silver chloride, silver carbonate, silver ammonia solution, silver hydroxide, silver citrate, and silver alkoxide.
[0066] The first fiber and the second fiber are both continuous straight filaments. In some embodiments, the diameter of the first fiber is 30 to 800 nm, for example, 30 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, or a range consisting of any two thereof, and the average pore size is 1 to 25 nm, for example, 1 nm, 2 nm, 5 nm, 10 nm, 20 nm, 25 nm, or a range consisting of any two thereof; and / or, the diameter of the second fiber is 1 to 10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or a range consisting of any two thereof, and the average pore size is 2 to 50 nm, for example, 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, or a range consisting of any two thereof. By limiting the diameter and average pore size of the first fiber and the second fiber, the air permeability and filtration performance of the polylactic acid fiber antibacterial membrane can be further improved.
[0067] Specifically, the diameter of the first fiber refers to the diameter of the cross section of a single first fiber, and the diameter of the second fiber refers to the diameter of the cross section of a single second fiber. Specifically, the surface of the polylactic acid fiber antibacterial film can be observed using a scanning electron microscope, and then the diameters of the first fiber and the second fiber can be measured, or the cross section of the polylactic acid fiber antibacterial film can be observed using a transmission electron microscope, and then the diameters of the first fiber and the second fiber can be measured.
[0068] The fiber contains voids, i.e., the pores of the fiber, which can be continuous or discontinuous. The size and distribution of the pores have an important influence on many properties of the fiber, such as air permeability, filtration performance, etc. The average pore size of the fiber refers to the average value of the size of the pores in the fiber. By limiting the average pore size of the first fiber and the second fiber, the air permeability and filtration performance of the polylactic acid fiber antibacterial membrane can be improved. In the specific implementation process of the present invention, the pore structure of the first fiber and the second fiber can be observed using scanning electron microscopy, transmission electron microscopy or X-ray tomography and other technologies. By measuring the size of the pores and calculating their average value, the average pore size of the first fiber and the second fiber can be obtained.
[0069] The first fiber and the second fiber are made of the same material, both containing left-handed polylactic acid (PLLA) and right-handed polylactic acid (PDLA). In some embodiments, the first fiber includes a first left-handed polylactic acid and a first right-handed polylactic acid, and the second fiber includes a second left-handed polylactic acid and a second right-handed polylactic acid; wherein the molar ratio of the second left-handed polylactic acid to the second right-handed polylactic acid is greater than the molar ratio of the first left-handed polylactic acid to the first right-handed polylactic acid. By limiting the molar ratio of the components in the first fiber and the second fiber, it is not only helpful to achieve the diameters of the first fiber and the second fiber of 30 to 800 nm and 1 to 10 μm, respectively, but also to take into account the improvement of mechanical properties and filtration performance.
[0070] By adjusting the ratio of left-handed polylactic acid and right-handed polylactic acid, the performance of the polylactic acid stereocomplex can be regulated to meet the needs of different application fields. As the content of right-handed polylactic acid increases, the ability to form a polylactic acid stereocomplex is enhanced, but when it increases to a certain extent, it may affect the improvement of other properties. In some embodiments, the molar ratio of the first left-handed polylactic acid to the first right-handed polylactic acid is (5-10):1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range consisting of any two thereof; and / or, the molar ratio of the second left-handed polylactic acid to the second right-handed polylactic acid is (10-15):1, for example, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 or a range consisting of any two thereof.
[0071] In some embodiments, the weight average molecular weight of the first L-polylactic acid is 10KDa to 150KDa; and / or, the weight average molecular weight of the first D-polylactic acid is 200KDa to 350KDa; and / or, the weight average molecular weight of the second L-polylactic acid is 50KDa to 200KDa; and / or, the weight average molecular weight of the second D-polylactic acid is 300KDa to 450KDa.
[0072] The present invention does not limit the specific parameters of the polylactic acid fiber antibacterial membrane, as long as the above requirements are met. In some embodiments, the thickness of the polylactic acid fiber antibacterial membrane is 20 to 600 μm. The size of the polylactic acid fiber antibacterial membrane can be adjusted according to actual needs to meet the application in different fields. In some embodiments, the breaking strength of the polylactic acid fiber antibacterial membrane is 15 to 34 MPa. It can be understood that the polylactic acid fiber antibacterial membrane has high mechanical strength. In some embodiments, at a temperature of 25°C and a humidity of 45%, the surface potential of the polylactic acid fiber antibacterial membrane is 8 to 17 kV. By limiting the surface potential of the polylactic acid fiber antibacterial membrane, it can better adsorb the substances to be filtered and improve the filtration efficiency. In some embodiments, the polylactic acid fiber antibacterial membrane has a high mechanical strength of 15 to 34 MPa. 0.3 and PM 2.5 The filtration efficiency is ≥98%. It can be understood that the polylactic acid fiber antibacterial membrane of the present invention has a great 0.3and PM 2.5 The particles have a high filtration efficiency. In some embodiments, at a gas flow rate of 10 to 85 L / min, the air resistance of the polylactic acid fiber antibacterial membrane is ≤80 Pa. By limiting the air resistance of the polylactic acid fiber antibacterial membrane, it has a lower air resistance at a certain gas flow rate, and can better achieve air exchange at a high filtration rate, and has higher air permeability. In some embodiments, under light with a wavelength of 600 nm, the antibacterial rate of the polylactic acid fiber antibacterial membrane against Escherichia coli and Staphylococcus aureus is ≥86%. It can be understood that the polylactic acid fiber antibacterial membrane has excellent antibacterial properties and can achieve long-term service.
[0073] The second aspect of the present invention provides a method for preparing a polylactic acid fiber antibacterial film, comprising the following steps:
[0074] The first spinning solution, the second spinning solution and the titanium dioxide dispersion are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film;
[0075] The first spinning solution and the second spinning solution both contain polylactic acid, the antibacterial particle dispersion contains titanium dioxide and / or modified titanium dioxide, and the mass fraction of polylactic acid in the second spinning solution is greater than the mass fraction of polylactic acid in the first spinning solution.
[0076] In the multi-needle electrospinning process, the first spinning solution and the second spinning solution are respectively formed into the first fiber and the second fiber, and the first fiber and the second fiber are randomly stacked. At the same time, titanium dioxide or modified titanium dioxide can be loaded on the surface of the first fiber and the second fiber.
[0077] Specifically, multi-needle electrostatic spinning can be implemented using a multi-needle electrostatic spinning device, which is usually composed of multiple nozzles, and each nozzle can be independently electrostatically spun. In the multi-needle electrostatic spinning process, the multi-needle electrostatic spinning device is started, so that the first spinning solution, the second spinning solution, and the antibacterial particle dispersion are ejected from the nozzle under the action of a high-voltage electrostatic field to form a charged jet stream. The jet stream is subjected to the effects of electric field force, surface tension, and air resistance during flight, and the first spinning solution and the second spinning solution are gradually stretched and refined, and the solvent evaporates, and finally deposited on the receiving device to form the first fiber and the second fiber, while titanium dioxide or modified titanium dioxide is attached to the first fiber and the second fiber surface in a spray state, and the solvent evaporates, and titanium dioxide or modified titanium dioxide is loaded on the first fiber and the second fiber surface. In addition, during the multi-needle electrospinning process, the first fibers and the second fibers need to be collected and sorted. For example, the deposition density and arrangement of the first fibers and the second fibers can be controlled by adjusting the movement speed and direction of the receiving device and the distance between the nozzle and the receiving device, so that the first fibers and the second fibers are randomly stacked to form a mesh fiber membrane.
[0078] The polylactic acid is mixed with a solvent, and the polylactic acid is fully dissolved by stirring or ultrasound to form a uniform spinning solution. In some embodiments, the method for preparing the first spinning solution includes: dissolving the first polylactic acid in a first solvent to obtain a first spinning solution; the method for preparing the second spinning solution includes: dissolving the second polylactic acid in a second solvent to obtain a second spinning solution; wherein the first polylactic acid and the second polylactic acid both include left-handed polylactic acid and right-handed polylactic acid. Specifically, the first polylactic acid includes a first left-handed polylactic acid and a first right-handed polylactic acid, and the second polylactic acid includes a second left-handed polylactic acid and a second right-handed polylactic acid, wherein the molar ratio of the second left-handed polylactic acid to the second right-handed polylactic acid is greater than the molar ratio of the first left-handed polylactic acid to the first right-handed polylactic acid.
[0079] Parameters such as the concentration, viscosity and surface tension of the spinning solution can be adjusted according to actual needs. In some preferred embodiments, the molar ratio of the first left-handed polylactic acid to the first right-handed polylactic acid is (5-10):1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 or a range consisting of any two of them; the molar ratio of the second left-handed polylactic acid to the second right-handed polylactic acid is (10-15):1, for example, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 or a range consisting of any two of them; in some preferred embodiments, the sum of the mass fractions of the first left-handed polylactic acid and the first right-handed polylactic acid in the first spinning solution is 5%-10%, for example, 5%, 6%, 8%, 10% or a range consisting of any two of them; the sum of the mass fractions of the second right-handed polylactic acid and the second left-handed polylactic acid in the second spinning solution is 10%-20%, for example, 10%, 15%, 20% or a range consisting of any two of them.
[0080] The present invention uses left-handed polylactic acid and right-handed polylactic acid as matrix polymers, and dissolves them in a mixed solvent composed of a good solvent and a non-good solvent to prepare a first spinning solution and a second spinning solution with a concentration gradient, which is helpful to achieve the preparation of the above-mentioned polylactic acid fiber antibacterial film with excellent performance. In some preferred embodiments, the first solvent includes a first good solvent and a first non-good solvent, and the volume ratio of the first good solvent to the first non-good solvent is 1: (2.5-5.5), such as 1: 2.5, 1: 3, 1: 4, 1: 5.5 or a range composed of any two thereof; the second solvent includes a second good solvent and a second non-good solvent, and the volume ratio of the second good solvent to the second non-good solvent is 1: (5.5-8.5), such as 1: 5.5, 1: 6, 1: 8.5 or a range composed of any two thereof.
[0081] By constructing a "non-good solvent-good solvent-polymer" ternary system, the principle of non-good solvent-induced phase separation can be used to generate three-dimensional interconnected pores on the fiber surface in situ, further reducing air resistance. Preferably, the first good solvent and the second good solvent independently include at least one of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate, and tetrahydrofuran, and the first non-good solvent and the second non-good solvent independently include at least one of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol, and propylene glycol. By further limiting the specific type of solvent, the performance of the polylactic acid fiber antibacterial film can be optimized.
[0082] In some embodiments, the preparation method of the antibacterial particle dispersion includes: mixing titanium dioxide and / or silver-doped titanium dioxide, a dispersant and a third solvent to obtain an antibacterial particle dispersion. The dispersant helps prevent the aggregation of titanium dioxide and / or silver-doped titanium dioxide particles and improves the stability of the dispersion. Among them, the dispersant includes at least one of polyvinyl pyrrolidone, dodecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the third solvent includes at least one of water, dimethylformamide, dichloromethane, chloroform, N-methylpyrrolidone, hexafluoroisopropanol, methanol, ethanol, isopropanol, and glycerol.
[0083] By adjusting the concentration of the dispersion, uneven spraying can be prevented from affecting the performance of the polylactic acid fiber antibacterial film. In some embodiments, the mass ratio of titanium dioxide and / or silver-doped titanium dioxide to the dispersant is 1: (10-100), such as 1: 10, 1: 20, 1: 50, 1: 80, 1: 100 or a range consisting of any two of them, preferably 1: (20-80); the mass fraction of titanium dioxide and / or silver-doped titanium dioxide in the dispersion is 0.15% to 1%, such as 0.15%, 0.5%, 0.75%, 1% or a range consisting of any two of them.
[0084] In the multi-needle electrospinning process, the first spinning solution, the second spinning solution, and the titanium dioxide dispersion need to be loaded into the container of the nozzle respectively, and ensure that the aperture of the nozzle meets the required fiber size. In some embodiments, in the multi-needle electrospinning process, the metal nozzles loaded with the first spinning solution, the second spinning solution, and the antibacterial particle dispersion are the first nozzle, the second nozzle, and the third nozzle respectively; the inner diameter of the first nozzle is 10 to 20 μm, the inner diameter of the second nozzle is 60 to 80 μm, and the inner diameter of the third nozzle is 30 to 60 μm.
[0085] In addition, in the multi-needle electrospinning process, a high voltage electrostatic field needs to be applied to charge the spinning solution. According to the properties and viscosity of the spinning solution, a suitable voltage range is selected. In some preferred embodiments, the voltages of the first nozzle, the second nozzle, and the third nozzle are all 10 to 30 kV.
[0086] By limiting the consumption rates of the first spinning solution, the first spinning solution and the titanium dioxide dispersion, the preparation of polylactic acid fiber antibacterial films with different mass ratios can be achieved. In some embodiments, the consumption rate of the first spinning solution is 0.8 to 2 mL / h, the consumption rate of the first spinning solution is 0.2 to 1.2 mL / h, and the consumption rate of the titanium dioxide dispersion is 0.2 to 1.5 mL / h.
[0087] The receiving device of multi-needle electrospinning can be a rotating drum, a flat plate or a mesh structure, etc. The distance of the receiving device will affect the deposition morphology and arrangement of the fibers. In some preferred embodiments, the receiving distances of the first nozzle, the second nozzle and the third nozzle are all 10 to 25 cm.
[0088] In some embodiments, the spinning temperature is 20-45° C., and the relative humidity of the environment is 25%-45%.
[0089] The third aspect of the present invention provides an air filter, comprising the polylactic acid fiber antibacterial membrane provided by the first aspect or the polylactic acid fiber antibacterial membrane prepared by the preparation method provided by the second aspect.
[0090] Due to the inclusion of the above-mentioned excellent polylactic acid fiber antibacterial membrane, the air filter can achieve PM 0.3 and PM 2.5 It can effectively intercept particles such as bacteria and has excellent antibacterial properties, achieving long-term service life.
[0091] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. The weight average molecular weight of left-handed polylactic acid (PLLA) is 10KDa to 200KDa; the weight average molecular weight of right-handed polylactic acid (PDLA) is 200KDa to 450KDa.
[0092] Example 1
[0093] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0094] Step S1, preparing a nano titanium dioxide dispersion: mixing titanium dioxide with an average diameter of 25 nm and dichloromethane, and then adding dodecyltrimethylammonium bromide dispersant to obtain a titanium dioxide dispersion (the mass ratio of titanium dioxide to dispersant is 1:60, and the mass fraction of titanium dioxide in the dispersion is 0.5wt%);
[0095] Step S2, preparing spinning solution A and spinning solution B: dissolving PLLA in a mixed solvent consisting of chloroform and methanol (the volume ratio of chloroform to methanol is 1:3) to prepare a spinning solution A with a concentration of 3wt%; dissolving PLLA in a mixed solvent consisting of N-methylpyrrolidone and glycerol (the volume ratio of N-methylpyrrolidone and glycerol is 1:6) to prepare a spinning solution B with a concentration of 17wt%;
[0096] Step S3, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.5:0.8, the titanium dioxide dispersion obtained in S1, the spinning solution A and the spinning solution B obtained in S2 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 20 μm; wherein the inner diameter of the nozzle used for the spinning solution A is 15 μm, the inner diameter of the nozzle used for the spinning solution B is 70 μm, the inner diameter of the nozzle used for the titanium dioxide dispersion is 55 μm, and the titanium dioxide dispersion is 10 μm. 2.5 mL of liquid was taken, 5 mL of spinning solution A and spinning solution B were taken, the electrospinning voltage was 20 kV, the relative humidity of the environment was 30%, the consumption rate of titanium dioxide dispersion was 0.8 mL / h, the consumption rate of spinning solution A was 1.0 mL / h, the consumption rate of spinning solution B was 0.5 mL / h, the receiving distance was 15 cm, the diameter of the first fiber obtained from spinning solution A was 50 nm, the average pore size was 3 nm, the diameter of the fiber obtained from spinning solution B was 1 μm, and the average pore size was 25 nm.
[0097] Example 2
[0098] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0099] S1, preparing a titanium dioxide dispersion: mixing titanium dioxide with an average diameter of 30 nm and chloroform, and then adding sodium dodecyl sulfate dispersant to obtain a titanium dioxide dispersion (the mass ratio of titanium dioxide to the dispersant is 1:40, and the mass fraction of titanium dioxide in the dispersion is 0.75 wt %);
[0100] S2, preparing spinning solution A and spinning solution B: PLLA is used as a matrix polymer, and is dissolved in a mixed solvent consisting of tetrahydrofuran and ethylene glycol (the volume ratio of tetrahydrofuran to ethylene glycol is 1:4) to prepare a spinning solution A with a concentration of 8 wt%, and is dissolved in a mixed solvent consisting of ethyl acetate and propylene glycol (the volume ratio of ethyl acetate to propylene glycol is 1:7) to prepare a spinning solution B with a concentration of 20 wt%;
[0101] S3, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.53:0.8, the titanium dioxide dispersion obtained in S1, the spinning solution A and the spinning solution B obtained in S2 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 300 μm; wherein the inner diameter of the nozzle used for the spinning solution A is 20 μm, the inner diameter of the nozzle used for the spinning solution B is 75 μm, the inner diameter of the nozzle used for the titanium dioxide dispersion is 45 μm, and the titanium dioxide dispersion is 10 μm. 3 mL of liquid was taken, 6 mL of spinning solution A and spinning solution B were taken, the electrospinning voltage was 25 kV, the relative humidity of the environment was 37%, the consumption rate of titanium dioxide dispersion was 1.2 mL / h, the consumption rate of spinning solution A was 1.5 mL / h, the consumption rate of spinning solution B was 0.8 mL / h, the receiving distance was 25 cm, the diameter of the first fiber obtained from spinning solution A was 800 nm, the average pore size was 5 nm, the diameter of the second fiber obtained from spinning solution B was 10 μm, and the average pore size was 35 nm.
[0102] Example 3
[0103] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0104] S1, preparing a titanium dioxide dispersion: mixing titanium dioxide with an average diameter of 40 nm and N-methylpyrrolidone, and then adding sodium dodecylbenzene sulfonate dispersant to obtain a titanium dioxide dispersion (the mass ratio of titanium dioxide to the dispersant is 1:20, and the mass fraction of titanium dioxide in the dispersion is 1 wt %);
[0105] S2, preparing spinning solution A and spinning solution B: dissolving PLLA in a mixed solvent consisting of ethyl acetate and ethanol (the volume ratio of ethyl acetate to ethanol is 1:5) to prepare a spinning solution A with a concentration of 10wt%; dissolving PLLA in a mixed solvent consisting of chloroform and propanol (the volume ratio of chloroform to propanol is 1:10) to prepare a spinning solution B with a concentration of 20wt%;
[0106] S3, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.6:1, the titanium dioxide dispersion obtained in S1, the spinning solution A and the spinning solution B obtained in S2 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 600 μm; the inner diameter of the nozzle used for the spinning solution A is 15 μm, the inner diameter of the nozzle used for the spinning solution B is 70 μm, the inner diameter of the nozzle used for the titanium dioxide dispersion is 30 μm, and the titanium dioxide dispersion is taken as The electrospinning voltage was 22 kV, the relative humidity was 45%, the consumption rate of titanium dioxide dispersion was 2 mL / h, the consumption rate of spinning solution A was 2 mL / h, the consumption rate of spinning solution B was 1.2 mL / h, the receiving distance was 22 cm, the first fiber obtained from spinning solution A had an average diameter of 500 nm and an average pore size of 15 nm, the fiber obtained from spinning solution B had an average diameter of 6 μm and an average pore size of 50 nm.
[0107] Example 4
[0108] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0109] S1, preparation of Ag-TiO2 particles: titanium sulfate, silver nitrate and water were mixed (the mass ratio of titanium sulfate to silver nitrate was 3:1), and then microwave-assisted synthesis of Ag-TiO2 was performed (the output power of the microwave reactor was 800 W, the reaction temperature was 180 ° C, the reaction time was 60 min, and the average diameter of Ag-TiO2 was 30 nm;
[0110] S2, preparing a Ag-TiO2 dispersion: mixing Ag-TiO2 with dimethylformamide, and then adding polyvinyl pyrrolidone dispersant to obtain a Ag-TiO2 dispersion (the mass ratio of Ag-TiO2 to the dispersant is 1:100, and the mass fraction of Ag-TiO2 in the dispersion is 0.25wt%);
[0111] S3, preparing spinning solutions A and B: mixing PDLA and PLLA at a molar ratio of 1:10, dissolving them in a mixed solvent consisting of dichloromethane and ethanol (the volume ratio of dichloromethane to ethanol is 1:2) to prepare a spinning solution A with a concentration of 0.4wt%; mixing PDLA and PLLA at a molar ratio of 1:15, dissolving them in a mixed solvent consisting of dimethylformamide and butanol (the volume ratio of dimethylformamide to butanol is 1:5) to prepare a spinning solution B with a concentration of 15wt%;
[0112] S4, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.25:0.25, the Ag-TiO2 dispersion obtained in S2, the spinning solution A and the spinning solution B obtained in S13 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 100 μm; wherein the inner diameter of the nozzle used for the spinning solution A is 10 μm, the inner diameter of the nozzle used for the spinning solution B is 80 μm, the inner diameter of the nozzle used for the Ag-TiO2 dispersion is 50 μm, and the inner diameter of the Ag-TiO2 2 mL of spinning solution, 4 mL of spinning solution A and spinning solution B, the electrospinning voltage is 10 kV, the spinning temperature is 20°C, the relative humidity of the environment is 25%, the consumption rate of Ag-TiO2 dispersion is 0.2 mL / h, the consumption rate of spinning solution A is 0.8 mL / h, the consumption rate of spinning solution B is 0.2 mL / h, the receiving distance is 17 cm, the diameter of the first fiber obtained from spinning solution A is 200 nm, the average pore size is 6 nm, the diameter of the fiber obtained from spinning solution B is 5 μm, and the average pore size is 2 nm.
[0113] Example 5
[0114] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0115] S1, preparation of Ag-TiO2 particles: titanium hydroxide and silver chloride were mixed with water (the mass ratio of titanium hydroxide to silver chloride was 5:1), and then microwave-assisted synthesis of Ag-TiO2 was performed (the output power of the microwave reactor was 700 W, the reaction temperature was 160 ° C, the reaction time was 80 min, and the average diameter of Ag-TiO2 was 32 nm;
[0116] S2, preparing a Ag-TiO2 dispersion: mixing Ag-TiO2 with dichloromethane, and then adding dodecyltrimethylammonium bromide as a dispersant to obtain a Ag-TiO2 dispersion (the mass ratio of Ag-TiO2 to the dispersant is 1:60, and the mass fraction of Ag-TiO2 in the dispersion is 0.5wt%);
[0117] S3, preparing spinning solutions A and B: PDLA and PLLA in a molar ratio of 1:7 are mixed, and dissolved in a mixed solvent consisting of chloroform and methanol (the volume ratio of chloroform and methanol is 1:3) to prepare a spinning solution A with a concentration of 5wt%; PDLA and PLLA in a molar ratio of 1:14 are mixed, and dissolved in a mixed solvent consisting of N-methylpyrrolidone and glycerol (the volume ratio of N-methylpyrrolidone and glycerol is 1:6) to prepare a spinning solution B with a concentration of 18wt%;
[0118] S4, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.2:0.8, the Ag-TiO2 dispersion obtained in S2, the spinning solution A and the spinning solution B obtained in S3 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 20 μm; wherein the inner diameter of the nozzle used for the spinning solution A is 15 μm, the inner diameter of the nozzle used for the spinning solution B is 70 μm, the inner diameter of the nozzle used for the Ag-TiO2 dispersion is 55 μm, and the Ag-TiO2 dispersion is taken as The electrospinning voltage was 20 kV, the spinning temperature was 25 °C, the relative humidity was 30%, the consumption rate of Ag-TiO2 dispersion was 0.8 mL / h, the consumption rate of spinning solution A was 1.0 mL / h, the consumption rate of spinning solution B was 0.5 mL / h, the receiving distance was 15 cm, the diameter of the first fiber obtained from spinning solution A was 50 nm, the average pore size was 4 nm, the diameter of the fiber obtained from spinning solution B was 1 μm, and the average pore size was 25 nm.
[0119] Example 6
[0120] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0121] S1, preparing Ag-TiO2 particles: ethyl titanate and silver hydroxide were mixed with water (the mass ratio of ethyl titanate to silver hydroxide was 8:1), and then Ag-TiO2 was synthesized by microwave-assisted method (the output power of microwave reactor was 1000 W, the reaction temperature was 100° C., the reaction time was 30 minutes, and the average diameter of Ag-TiO2 was 35 nm);
[0122] S2, preparing a Ag-TiO2 dispersion: mixing Ag-TiO2 with chloroform, and then adding sodium dodecyl sulfate dispersant to obtain a Ag-TiO2 dispersion (the mass ratio of Ag-TiO2 to the dispersant is 1:40, and the mass fraction of Ag-TiO2 in the solution is 0.75wt%);
[0123] S3, preparing spinning solution A and spinning solution B: PDLA and PLLA in a molar ratio of 1:6 are mixed, and dissolved in a mixed solvent consisting of dimethylformamide and isopropanol (the volume ratio of dimethylformamide and isopropanol is 1:4) to prepare a spinning solution A with a concentration of 10wt%; PDLA and PLLA in a molar ratio of 1:12 are mixed, and dissolved in a mixed solvent consisting of ethyl acetate and propylene glycol (the volume ratio of ethyl acetate and propylene glycol is 1:7) to prepare a spinning solution B with a concentration of 20wt%;
[0124] S4, preparation of polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.4:0.33, the Ag-TiO2 dispersion obtained in S2, the spinning solution A and the spinning solution B obtained in S3 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 600 μm; wherein the inner diameter of the nozzle used for spinning solution A is 20 μm, the inner diameter of the nozzle used for spinning solution B is 75 μm, the inner diameter of the nozzle used for Ag-TiO2 dispersion is 45 μm, and the inner diameter of the nozzle used for Ag-TiO2 spinning is 50 μm. 3 mL of liquid was taken, 6 mL of spinning solution A and spinning solution B were taken, the electrospinning voltage was 25 kV, the spinning temperature was 30°C, the relative humidity of the environment was 37%, the consumption rate of Ag-TiO2 dispersion was 0.5 mL / h, the consumption rate of spinning solution A was 1.5 mL / h, the consumption rate of spinning solution B was 0.6 mL / h, the receiving distance was 25 cm, the diameter of the fiber obtained from spinning solution A was 800 nm, the average pore size was 20 nm, the diameter of the fiber obtained from spinning solution B was 10 μm, and the average pore size was 35 nm.
[0125] Example 7
[0126] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0127] S1, preparing Ag-TiO2 particles: diisopropyl titanate and silver carbonate were mixed with water (the mass ratio of diisopropyl titanate to silver carbonate was 12:1), and then microwave-assisted synthesis of Ag-TiO2 particles was performed (the output power of the microwave reactor was 500 W, the reaction temperature was 120°C, the reaction time was 120 minutes, and the average diameter of Ag-TiO2 was 38 nm);
[0128] S2, preparing a Ag-TiO2 dispersion: dissolving Ag-TiO2 in N-methylpyrrolidone, and then adding sodium dodecylbenzenesulfonate dispersant to obtain a Ag-TiO2 dispersion (the mass ratio of Ag-TiO2 to the dispersant is 1:20, and the mass of Ag-TiO2 in the solution is 1wt%);
[0129] S3, preparing spinning solution A and spinning solution B: PDLA and PLLA with a molar ratio of 1:5 are mixed, and dissolved in a mixed solvent consisting of chloroform and n-butanol (the volume ratio of chloroform and n-butanol is 1:4.5) to prepare a spinning solution A with a concentration of 10wt%; PDLA and PLLA with a molar ratio of 1:10 are mixed, and dissolved in a mixed solvent consisting of tetrahydrofuran and ethylene glycol (the volume ratio of tetrahydrofuran and ethylene glycol is 1:8.5) to prepare a spinning solution B with a concentration of 20wt%;
[0130] S4, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:0.6:0.75, the Ag-TiO2 dispersion obtained in S2, the spinning solution A and the spinning solution B obtained in S3 are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 200 μm; wherein the inner diameter of the nozzle used for the spinning solution A is 15 μm, the inner diameter of the nozzle used for the spinning solution B is 65 μm, the inner diameter of the nozzle used for the Ag-TiO2 dispersion is 30 μm, and the Ag-TiO2 dispersion is 10 μm. 2.5 mL of the dispersion was taken, 5 mL of both spinning solution A and spinning solution B were taken, the electrospinning voltage was 22 kV, the spinning temperature was 35 ° C, the ambient relative humidity was 45%, the consumption rate of Ag-TiO2 dispersion was 1.5 mL / h, the consumption rate of spinning solution A was 2 mL / h, the consumption rate of spinning solution B was 1.2 mL / h, the receiving distance was 22 cm, the diameter of the fiber obtained from spinning solution A was 300 nm, the average pore size was 25 nm, the diameter of the fiber obtained from spinning solution B was 8 μm, and the average pore size was 50 nm.
[0131] Comparative Example 1
[0132] S1, dissolving PLLA in a mixed solvent consisting of dimethylformamide and methanol (the volume ratio of dimethylformamide to methanol is 1:4) to prepare a spinning solution A with a concentration of 2wt%, and dissolving PLLA in a mixed solvent consisting of N-methylpyrrolidone and isopropanol (the volume ratio of N-methylpyrrolidone and isopropanol is 1:9) to prepare a spinning solution B with a concentration of 12wt%;
[0133] S2, according to the mass ratio of the formed first fiber and the second fiber of 1:0.5, the spinning solution A and the spinning solution B are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 400μm; wherein, the inner diameter of the nozzle used for spinning solution A is 12μm, the inner diameter of the nozzle used for spinning solution B is 62μm, 4mL of spinning solution A and spinning solution B are taken, the electrospinning voltage is 18kV, the relative humidity of the environment is 33%, the consumption rate of spinning solution A is 0.6mL / h, the consumption rate of spinning solution B is 0.3mL / h, the receiving distance is 19cm, the diameter of the first fiber obtained from spinning solution A is 350nm, the average pore size is 22nm, the diameter of the second fiber obtained from spinning solution B is 5μm, and the average pore size is 25nm.
[0134] Comparative Example 2
[0135] S1, preparing a nano titanium dioxide dispersion: mixing titanium dioxide with an average diameter of 32 nm and dichloromethane, and then adding dodecyltrimethylammonium bromide as a dispersant to obtain a titanium dioxide dispersion (the mass ratio of titanium dioxide to the dispersant is 1:20, and the mass fraction of titanium dioxide in the dispersion is 0.8 wt %);
[0136] S2, dissolving PLLA in a mixed solvent consisting of chloroform and butanol (the volume ratio of chloroform and butanol is 1:3) to prepare a spinning solution A with a concentration of 10wt%; dissolving PLLA in a mixed solvent consisting of ethyl acetate and ethanol (the volume ratio of ethyl acetate and ethanol is 1:8) to prepare a spinning solution B with a concentration of 22wt%; adding titanium dioxide dispersion to the spinning solution A and the spinning solution B, respectively, to obtain spinning solutions C and D;
[0137] S3, preparation of polylactic acid fiber antibacterial film: multi-needle electrospinning of spinning solution C and spinning solution D to obtain a polylactic acid fiber antibacterial film with a thickness of 350μm; wherein, the inner diameter of the spinning nozzle used for spinning solution C is 18μm, the inner diameter of the nozzle used for spinning solution D is 76μm, 2.5mL of titanium dioxide dispersion is taken, 4mL of spinning solution A and spinning solution B are taken, the electrospinning voltage is 12kV, the relative humidity of the environment is 42%, the consumption rate of spinning solution C is 0.3mL / h, the consumption rate of spinning solution D is 0.7mL / h, the receiving distance is 14cm, the diameter of the first fiber obtained from spinning solution C is 680nm, the average pore size is 18nm, the diameter of the second fiber obtained from spinning solution D is 8μm, and the average pore size is 40nm.
[0138] Comparative Example 3
[0139] S1, PDLA and PLLA with a molar ratio of 1:8 are mixed and dissolved in a mixed solvent consisting of dichloromethane and glycerol (the volume ratio of dichloromethane and glycerol is 1:3) to prepare a spinning solution A with a concentration of 6wt%; PDLA and PLLA with a molar ratio of 1:13 are mixed and dissolved in a mixed solvent consisting of N-methylpyrrolidone and n-butanol (the volume ratio of N-methylpyrrolidone and n-butanol is 1:8) to prepare a spinning solution B with a concentration of 14wt%;
[0140] S2, according to the mass ratio of the first fiber and the second fiber formed being 1:0.4, the spinning solution A and the spinning solution B are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 400μm; wherein, the inner diameter of the nozzle used for the spinning solution A is 12μm, the inner diameter of the nozzle used for the spinning solution B is 62μm, the spinning solution A and the spinning solution B are both taken 4mL, the electrospinning voltage is 18kV, the spinning temperature is 40℃, the relative humidity of the environment is 33%, the consumption rate of the spinning solution A is 0.5mL / h, the consumption rate of the spinning solution B is 0.2mL / h, and the receiving distance is 19cm. The diameter of the fiber obtained from the spinning solution A is 400nm, the average pore size is 16nm, and the diameter of the fiber obtained from the spinning solution B is 7μm, and the average pore size is 25nm.
[0141] Comparative Example 4
[0142] S1, mixing isopropyl titanate and silver citrate with water (the mass ratio of isopropyl titanate to silver citrate is 9:1), dissolving Ag-TiO2 in dichloromethane, and then adding dodecyltrimethylammonium bromide dispersant to obtain Ag-TiO2 dispersion (the average diameter of Ag-TiO2 is 34 nm, and the mass fraction of Ag-TiO2 in the dispersion is 0.5wt%);
[0143] S2, PDLA and PLLA in a molar ratio of 1:9 are mixed and dissolved in a mixed solvent consisting of dimethylformamide and butanol (the volume ratio of dimethylformamide and butanol is 1:5) to prepare a spinning solution A with a concentration of 6wt%; PDLA and PLLA in a molar ratio of 1:11 are mixed and dissolved in a mixed solvent consisting of dichloromethane and ethanol (the volume ratio of dichloromethane and ethanol is 1:9) to prepare a spinning solution B with a concentration of 12wt%; then, the Ag-TiO2 dispersion is added to the spinning solution A and the spinning solution B, respectively, to obtain spinning solutions C and D;
[0144] S3, according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:2:1.5, the spinning solution C and the spinning solution D are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 80 μm; wherein, the inner diameter of the spinning nozzle used for spinning solution A is 18 μm, the inner diameter of the spinning nozzle used for spinning solution B is 76 μm, 2.5 mL of both spinning solution A and spinning solution B are taken, the electrospinning voltage is 12 kV, the spinning temperature is 45°C, the relative humidity of the environment is 42%, the consumption rate of spinning solution A is 0.4 mL / h, the consumption rate of spinning solution B is 0.8 mL / h, the receiving distance is 14 cm, the diameter of the fiber obtained from spinning solution A is 350 nm, the average pore size is 13 nm, the diameter of the fiber obtained from spinning solution B is 5 μm, and the average pore size is 40 nm.
[0145] Comparative Example 5
[0146] The difference from Example 1 is that the average diameter of titanium dioxide is 5 nm.
[0147] Comparative Example 6
[0148] The difference from Example 1 is that the average diameter of titanium dioxide is 150 nm.
[0149] Comparative Example 7
[0150] The difference from Example 1 is that only the titanium dioxide dispersion and the spinning solution A are used for multi-needle electrospinning.
[0151] Comparative Example 8
[0152] The difference from Example 1 is that titanium dioxide is replaced by Zr-MOFs nanocrystals (crystal size is 200 nm, pore diameter is 1.2 nm).
[0153] Comparative Example 9
[0154] The difference from Example 1 is that the inner diameter of the nozzle used for spinning solution A is 6 μm, the inner diameter of the nozzle used for spinning solution B is 200 μm, the diameter of the first fiber formed by spinning solution A is 120 nm, and the average pore size is 10 nm; the diameter of the second fiber formed by spinning solution B is 12 μm, and the average pore size is 100 nm.
[0155] Comparative Example 10
[0156] The method for preparing the polylactic acid fiber antibacterial film of this embodiment comprises the following steps:
[0157] Step S1, preparing a nano titanium dioxide dispersion: mixing titanium dioxide with an average diameter of 20 nm and dimethylformamide, and then adding polyvinyl pyrrolidone dispersant to obtain a titanium dioxide dispersion (the mass ratio of titanium dioxide to dispersant is 1:80, and the mass fraction of titanium dioxide in the dispersant is 0.25wt%);
[0158] Step S2, preparing spinning solution A and spinning solution B: dissolving PLLA in a mixed solvent consisting of dichloromethane and ethanol (the volume ratio of dichloromethane to ethanol is 1:2.5) to prepare a spinning solution A with a concentration of 5wt%; dissolving PLLA in a mixed solvent consisting of dimethylformamide and butanol (the volume ratio of dimethylformamide to butanol is 1:5.5) to prepare a spinning solution B with a concentration of 10wt%;
[0159] Step S3, preparing a polylactic acid fiber antibacterial film: according to the mass ratio of the formed first fiber, the second fiber and the antibacterial particles being 1:1:4, the titanium dioxide spinning solution obtained in S1, the spinning solution A obtained in S2 and the spinning solution B are subjected to multi-needle electrospinning to obtain a polylactic acid fiber antibacterial film with a thickness of 100 μm; wherein the inner diameter of the nozzle used for the spinning solution A is 10 μm, the inner diameter of the nozzle used for the spinning solution B is 80 μm, the inner diameter of the nozzle used for the titanium dioxide dispersion is 50 μm, and the titanium dioxide dispersion is taken as 2 mL, 4 mL of spinning solution A and spinning solution B are taken, the electrospinning voltage is 10 kV, the relative humidity of the environment is 25%, the consumption rate of titanium dioxide dispersion is 0.2 mL / h, the consumption rate of spinning solution A is 0.8 mL / h, the consumption rate of spinning solution B is 0.2 mL / h, the receiving distance is 17 cm, the diameter of the first fiber formed by spinning solution A is 200 nm, the average pore size is 2 nm, the diameter of the second fiber formed by spinning solution B is 2 μm, and the average pore size is 10 nm.
[0160] Test example
[0161] 1. Tensile performance test
[0162] The polylactic acid fiber antibacterial film was cut to obtain tensile specimens, and its tensile properties were tested using a universal tensile machine (model 4403, sensor 100N) according to the ASTM D638-2003 plastic tensile properties test standard of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.
[0163] 2. Surface potential test
[0164] The surface potential of the polylactic acid fiber antibacterial film was tested using a non-contact electrostatic meter (VM54XQS, Quatek, USA). The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.
[0165] 3. Filtration performance test
[0166] The polylactic acid fiber antibacterial film (area 113.04cm2) was tested using the LZC-K automatic filter material tester (Suzhou Huada Instrument Equipment Co., Ltd.). 2 ) air filtration performance, the gas flow rate was set to 85L / min, and the particle size range of NaCl atomized particles produced by the aerosol generator was 0.1-10μm. At least 3 different positions of each group of fiber membranes were tested, and the results were averaged.
[0167] 4. Air resistance test
[0168] Respiratory resistance test: A micromanometer (AIRPRO AP800, TSI, USA), anthropomorphic respirator and simulated human head were used to measure respiratory resistance. The gas flow rate was set to 10, 32, 65, and 85 L / min. The filter membrane was encapsulated on a simulated human head, and the air pressure of the cavity composed of the filter material and the human head and the atmosphere were measured and subtracted. The experiment was repeated three times and the average value was taken to calculate the respiratory resistance (i.e., air resistance) of the filter membrane.
[0169] 5. Antibacterial performance test
[0170] The selected strains were Escherichia coli and Staphylococcus aureus, and the strains were cultured in lysate broth (LB) medium at 37°C for 16 h. After incubation, 0.5 mL of Escherichia coli and 0.5 mL of Staphylococcus aureus were washed, combined, and suspended in 0.85% NaCl solution to obtain 1 mL of cell mixture with a cell density of 10 9 CFU / mL. Then dilute 10 times with the above NaCl solution to a cell density of 10 8CFU / mL. The polylactic acid fiber antibacterial film was cut into discs with a diameter of 10 cm and immersed in 100 μL of bacterial suspension. The polylactic acid fiber antibacterial film was treated with light irradiation using a solar simulator (HSX-F300, NBeT). The optical density was measured using a solar power meter (VLP-2000, NBeT). The sample was kept at 25 cm from the light and irradiated for 30 minutes under light with a wavelength of 600 nm. The temperature was detected using a thermal imaging camera (HT-18, HTI). A control group was also set up (without antibacterial effect under sunlight). The bacterial suspension was serially diluted and the CFU counted until the cell density was about 10 2 CFU / mL, the plates were cultured overnight (37°C, RH75%), and the antibacterial efficiency was calculated by counting CFU. Three experiments were performed in each group, and the results were averaged.
[0171] The morphological and structural parameters of the polylactic acid fiber antibacterial films of the embodiments and comparative examples are shown in Table 1, and the test results are shown in Table 2 and Table 3.
[0172] Table 1
[0173]
[0174] Table 2
[0175]
[0176]
[0177] Table 3
[0178]
[0179] Figure 1 This is a SEM image of the polylactic acid fiber antibacterial film in Example 1 of the present invention; Figure 2 This is a SEM image of the polylactic acid fiber antibacterial film in Example 4 of the present invention; Figure 3 This is a SEM image of the polylactic acid fiber membrane in Comparative Example 2 of the present invention; Figure 4 It is a SEM picture of the polylactic acid fiber membrane in comparative example 4 of the present invention. Table 2 is the test results of mechanical properties, surface potential, filtration performance, and air resistance of the polylactic acid fiber antibacterial membrane of the embodiment and the comparative example, and Table 3 is the test results of antibacterial efficiency of the polylactic acid fiber antibacterial membrane of the embodiment and the comparative example.
[0180] According to Table 2, the breaking strength of the fiber filtration membrane of Examples 1 to 3 is 17.6 to 25.5 MPa, which is much greater than that of Comparative Examples 1 to 2. As the mass content of titanium dioxide increases, the breaking strength of the fiber membrane increases first and then decreases. This is mainly because when the titanium dioxide content is low, the addition of the dispersant can make it evenly dispersed in the solution. The dispersed titanium dioxide plays a role in crystallization and formation of crystal nuclei in the polymer, which helps to increase the crystallinity of the polylactic acid fiber and increase the physical crosslinking points in the molecule, thus playing a reinforcing role. However, the increase in crystallinity will correspondingly lead to a decrease in the toughness of the fiber membrane. When the titanium dioxide content is too high, it cannot be evenly dispersed, causing local agglomeration, increasing the stress concentration points of the fiber, and weakening the crystallization effect, resulting in a decrease in the breaking strength. Therefore, adding an appropriate amount of titanium dioxide helps to improve the strength of the nanofiber membrane.
[0181] The breaking strength of the fiber filtration membrane of Examples 4 to 7 is 22.6 to 33.5 MPa, which is much greater than that of Comparative Examples 3 to 4. As the content of Ag-TiO2 increases, the breaking strength of the fiber membrane increases first and then decreases. This is mainly because when Ag-TiO2 is low, the addition of a dispersant can make it evenly dispersed in the solution. The dispersed Ag-TiO2 plays a role in crystallization and formation of crystal nuclei in the polymer, which helps to increase the crystallinity of the polylactic acid fiber and increase the physical crosslinking points in the molecule, thus playing a reinforcing role. However, the increase in crystallinity will correspondingly lead to a decrease in the toughness of the fiber membrane. When the content of Ag-TiO2 is too large, it cannot be evenly dispersed, causing local agglomeration, increasing the stress concentration points of the fiber, and weakening the crystallization effect, resulting in a decrease in the breaking strength. Therefore, adding an appropriate amount of Ag-TiO2 helps to improve the strength of the nanofiber membrane. In addition, PDLA and PLLA are blended to form a stereocomplex of polylactic acid. As the content of PDLA increases, its ability to form stereocomplex crystals is enhanced, so that the fiber membrane has good breaking strength and a balanced tensile yield strength.
[0182] According to Table 2, the fiber filter membranes of Examples 1 to 3 have extremely high surface potentials (8.4 to 16.6 kV) and hardly decay over time, while the surface potential of Comparative Example 1 is relatively low. Although the fiber filter membrane of Comparative Example 2 has a relatively high surface potential, it decays severely over time. This indicates that the fiber filter membrane of the present invention has a relatively high surface potential and extremely high long-term stability. The ultra-high surface potential and enhanced nanofiber constraint properties make microporous nanofibers an ideal platform for molecular screening and adsorption separation, and they usually exhibit stronger load capacity and lower mass transfer resistance.
[0183] Examples 1 to 7 Fiber filtration membranes for PM 0.3 and PM 2.5 The filtration efficiency of the comparative examples 1 to 4 is above 98%. 0.3 and PM 2.5 The filtration efficiency is less than 80%.
[0184] Table 2 shows the antibacterial efficiency of the fiber filtration membranes of the embodiments and comparative examples against Escherichia coli and Staphylococcus aureus under illumination and without illumination. The antibacterial effect of the pure polylactic acid nanofiber membrane of comparative example 1 on Escherichia coli and Staphylococcus aureus is not obvious. The antibacterial rate of Escherichia coli under illumination is 21.9%, and the antibacterial rate of Staphylococcus aureus is 23.6%, but with the introduction of titanium dioxide, the antibacterial rate of Escherichia coli and Staphylococcus aureus has increased. Under no-light conditions, the antibacterial efficiency of the fiber membrane is not obvious, but under illumination, the antibacterial efficiency of the fiber membrane increases significantly, because nano-titanium dioxide can excite its surface electrons to undergo energy level transitions after photocatalysis, forming photogenerated holes with super strong oxidation ability and photogenerated electrons with super strong reduction ability. Photogenerated holes or photogenerated electrons combine with H2O or O2 on the surface of the material, and through a series of reactions, active substances such as hydroxyl radicals and superoxide ion radicals are generated, which combine with bacteria to decompose them.
[0185] Examples 4 to 7 and Comparative Example 4 all exhibited extremely high surface potentials (8.5 to 14.8 kV) and showed almost no decay over time, demonstrating extremely high long-term stability. The ultra-high surface potential and enhanced nanofiber confinement properties make microporous nanofibers an ideal platform for molecular sieving and adsorption separation, usually showing stronger loading capacity and lower mass transfer resistance. 0.3 and PM 2.5 The filtration efficiency of the fiber membrane is above 98%. 0.3 and PM 2.5 The filtration efficiency is lower than that at high potential, and the filtration efficiency of PM 0.3 The filtration efficiency is 70.3% for PM 2.5 The filtration efficiency is 72.4%.
[0186] In Table 2, Examples 4 to 7 and Comparative Examples 3 to 4 show the antibacterial efficiency of the fiber membrane against Escherichia coli and Staphylococcus aureus under illumination and without illumination. The antibacterial effect of the pure stereocomposite polylactic acid nanofiber membrane on Escherichia coli and Staphylococcus aureus is not obvious, with an antibacterial rate of 21.9% for Escherichia coli and 23.6% for Staphylococcus aureus, but with the increase of Ag-TiO2 content, the antibacterial rate of Escherichia coli and Staphylococcus aureus increased. Under no-light conditions, the antibacterial efficiency of the fiber membrane is not obvious, but under illumination, the antibacterial efficiency of the fiber membrane increases significantly, because the photocatalytic properties of titanium dioxide nanoparticles significantly improve the antibacterial effect of the fiber membrane after illumination. Silver nanoparticles can penetrate and kill bacteria by attaching to the cell membrane. In addition, the large surface area of silver nanoparticles also effectively inhibits the growth of bacteria.
[0187] Comparative Examples 2 and 4 both use blends for electrospinning, and most of the crystals are embedded in the polymer, which makes it difficult to load and is not conducive to function, resulting in poor filtration performance and antibacterial effect of the fiber filtration membrane.
[0188] This shows that the present invention constructs a "non-good solvent-good solvent-polymer" ternary system, and generates three-dimensional interconnected pores on the surface of polylactic acid nanofibers in situ through non-good solvent-induced phase separation, thereby obtaining a fiber filtration membrane with low air resistance; the formed stereocomposite crystals enhance the mechanical properties and filtration performance of the fiber membrane, obtain good interface compatibility through physical interaction, and have high crystallinity and a well-arranged microstructure; thanks to the photocatalytic properties of TiO2 and Ag-TiO2, the fiber membrane doped with nano-titanium dioxide has good antibacterial properties.
[0189] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A polylactic acid fiber antibacterial film, characterized in that: The polylactic acid fiber antibacterial film comprises first fibers, second fibers and antibacterial particles, the first fibers and the second fibers are randomly stacked, and the antibacterial particles are loaded on the surfaces of the first fibers and the second fibers; Among them, the diameter ratio of the first fiber to the second fiber is 1: (11-30), and the average diameter of the antibacterial particles is 10-100 nm; the first fiber and the second fiber both include polylactic acid, and the material of the antibacterial particles is titanium dioxide and / or modified titanium dioxide.
2. The polylactic acid fiber antibacterial film according to claim 1, characterized in that: The modified titanium dioxide is silver-doped titanium dioxide; The mass content of silver in the silver-doped titanium dioxide is 0.1% to 5%; Preferably, the preparation of the silver-doped titanium dioxide comprises: mixing a titanium source, a silver salt and water, and subjecting the mixture to microwave treatment to obtain the silver-doped titanium dioxide; Preferably, the mass ratio of the titanium source to the silver salt is (2-12):1; Preferably, the titanium source includes at least one of titanium sulfate, titanium hydroxide, titanium chloride, ethyl titanate, diisopropyl titanate, isopropyl titanate, and tetrabutyl titanate; Preferably, the silver salt comprises at least one of silver nitrate, silver chloride, silver carbonate, silver ammonia solution, silver hydroxide, silver citrate, and silver alkoxide; Preferably, the microwave treatment has a power of 500-1500 W, a temperature of 100-200° C., and a time of 20-120 min.
3. The polylactic acid fiber antibacterial film according to claim 1, characterized in that: The mass ratio of the first fiber, the second fiber and the antibacterial particles is 1:(0.2-2):(0.25-4); and / or, The thickness of the polylactic acid fiber antibacterial film is 20 to 600 μm.
4. The polylactic acid fiber antibacterial film according to claim 1, characterized in that: The diameter of the first fiber is 30-800 nm, and the average pore size is 1-25 nm; and / or the diameter of the second fiber is 1-10 μm, and the average pore size is 2-50 nm.
5. The polylactic acid fiber antibacterial film according to any one of claims 1 to 4, characterized in that: The first fiber and the second fiber both include left-handed polylactic acid and right-handed polylactic acid; Preferably, the first fiber comprises a first left-handed polylactic acid and a first right-handed polylactic acid, and the second fiber comprises a second left-handed polylactic acid and a second right-handed polylactic acid; Wherein, the molar ratio of the second L-polylactic acid to the second D-polylactic acid is greater than the molar ratio of the first L-polylactic acid to the first D-polylactic acid; Preferably, the molar ratio of the first L-polylactic acid to the first D-polylactic acid is (5-10):1; Preferably, the molar ratio of the second L-polylactic acid to the second D-polylactic acid is (10-15):
1.
6. A method for preparing the polylactic acid fiber antibacterial film according to any one of claims 1 to 5, characterized in that: The following steps are involved: The first spinning solution, the second spinning solution and the antibacterial particle dispersion are subjected to multi-needle electrospinning to obtain the polylactic acid fiber antibacterial film; Wherein, the first spinning solution and the second spinning solution both contain polylactic acid, the antibacterial particle dispersion contains titanium dioxide and / or modified titanium dioxide, and the mass fraction of polylactic acid in the second spinning solution is greater than the mass fraction of polylactic acid in the first spinning solution.
7. The preparation method according to claim 6, characterized in that: The preparation method of the first spinning solution comprises: dissolving the first polylactic acid in a first solvent to obtain the first spinning solution; The preparation method of the second spinning solution comprises: dissolving the second polylactic acid in a second solvent to obtain the second spinning solution; Preferably, the first polylactic acid and the second polylactic acid both include left-handed polylactic acid and right-handed polylactic acid; Preferably, the first polylactic acid comprises a first left-handed polylactic acid and a first right-handed polylactic acid, and the second polylactic acid comprises a second left-handed polylactic acid and a second right-handed polylactic acid; wherein the molar ratio of the second left-handed polylactic acid to the second right-handed polylactic acid is greater than the molar ratio of the first left-handed polylactic acid to the first right-handed polylactic acid; Preferably, the molar ratio of the first L-polylactic acid to the first D-polylactic acid is (5-10):1; Preferably, the sum of the mass fractions of the first L-polylactic acid and the first D-polylactic acid in the first spinning solution is 5% to 10%; Preferably, the first solvent includes a first good solvent and a first non-good solvent, and the volume ratio of the first good solvent to the first non-good solvent is 1:(2.5-4.5); Preferably, the molar ratio of the second L-polylactic acid to the second D-polylactic acid is (10-15):1; Preferably, the sum of the mass fractions of the second right-handed polylactic acid and the second left-handed polylactic acid in the second spinning solution is 10% to 20%; Preferably, the second solvent includes a second good solvent and a second non-good solvent, and the volume ratio of the second good solvent to the second non-good solvent is 1:(5.5-8.5); Preferably, the first good solvent and the second good solvent each independently include at least one of dichloromethane, chloroform, dimethylformamide, N-methylpyrrolidone, hexafluoroisopropanol, ethyl acetate, and tetrahydrofuran, and the first non-good solvent and the second non-good solvent each independently include at least one of methanol, ethanol, isopropanol, glycerol, butanol, ethylene glycol, and propylene glycol.
8. The preparation method according to claim 6, characterized in that: The preparation method of the antibacterial particle dispersion comprises: Mixing titanium dioxide and / or silver-doped titanium dioxide, a dispersant and a third solvent to obtain the antibacterial particle dispersion; Preferably, the dispersant includes at least one of polyvinyl pyrrolidone, dodecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; Preferably, the third solvent includes at least one of water, dimethylformamide, dichloromethane, chloroform, N-methylpyrrolidone, hexafluoroisopropanol, methanol, ethanol, isopropanol, and glycerol; Preferably, the mass ratio of the titanium dioxide and / or silver-doped titanium dioxide to the dispersant is 1:(20-80); Preferably, the mass fraction of the titanium dioxide and / or silver-doped titanium dioxide in the antibacterial particle dispersion is 0.15% to 1%.
9. The preparation method according to claim 6, characterized in that: In the multi-needle electrospinning process, the metal nozzles loaded with the first spinning solution, the second spinning solution and the antibacterial particle dispersion are respectively the first nozzle, the second nozzle and the third nozzle; Preferably, the inner diameter of the first nozzle is 10-20 μm, the inner diameter of the second nozzle is 60-80 μm, and the inner diameter of the third nozzle is 30-60 μm; Preferably, the voltages of the first nozzle, the second nozzle and the third nozzle are all 10-30 kV; Preferably, the consumption rate of the first spinning solution is 0.5 to 2 mL / h, the consumption rate of the second spinning solution is 0.2 to 1.2 mL / h, and the consumption rate of the titanium dioxide dispersion is 0.2 to 1.5 mL / h; Preferably, the receiving distances of the first nozzle, the second nozzle and the third nozzle are all 10-25 cm.
10. An air filter, characterized in that: The invention comprises the polylactic acid fiber antibacterial film according to any one of claims 1 to 5 or the polylactic acid fiber antibacterial film prepared by the preparation method according to any one of claims 6 to 9.